New benzoxazole derivatives as potential VEGFR-2 inhibitors and apoptosis inducers: design, synthesis, anti-proliferative evaluation, flowcytometric analysis, and in silico studies - Hazem Elkady; Alaa Elwan; Hesham A. El-Mahdy; Ahmed S. Doghish; Ahmed Ismail; Mohammed S. Taghour; Eslam B. Elkaeed; Ibrahim H. Eissa; Mohammed A. Dahab; Hazem A. Mahdy; Mohamed M. Khalifa (Taylor & Francis Group, 2022)
A new series of benzoxazole derivatives were designed and synthesised to have the main essential pharmacophoric features of VEGFR-2 inhibitors. Cytotoxic activities were evaluated for all derivatives against two human cancer cell lines, MCF-7 and HepG2. Also, the effect of the most cytotoxic derivatives on VEGFR-2 protein concentration was assessed by ELISA. Compounds 14o, 14l, and 14b showed the highest activities with VEGFR-2 protein concentrations of 586.3, 636.2, and 705.7 pg/ml, respectively. Additionally, the anti-angiogenic property of compound 14b against human umbilical vascular endothelial cell (HUVEC) was performed using a wound healing migration assay. Compound 14b reduced proliferation and migratory potential of HUVEC cells. Furthermore, compound 14b was subjected to further biological investigations including cell cycle and apoptosis analyses. Compound 14b arrested the HepG2 cell growth at the Pre-G1 phase and induced apoptosis by 16.52%, compared to 0.67% in the control (HepG2) cells. The effect of apoptosis was buttressed by a 4.8-fold increase in caspase-3 level compared to the control cells. Besides, different in silico docking studies were also performed to get better insights into the possible binding mode of the target compounds with VEGFR-2 active sites.